Role of Van der Waals forces in graphene adsorption over: Pd, Pt, Ni - Quiroga, María Alejandra (2013)
We report ab initio computations with the Vienna Ab initio Simulation Package (VASP) aimed at elucidating the adsorption mechanism of graphene-like structures on (111) Pd, Pt, and Ni surfaces. To study the adsorption properties, we simulate an already-formed graphene layer. We present a comparative discussion of the graphene interactions with the three metals, focusing on the very particular adsorption of graphene over Pd